A case of reversible drug‐induced liver failure. Issue 7 (2nd June 2017) - Ansari, Mohammad; Arshed, Sabrina; Islam, Mohammed; Sen, Shuvendu; Yousif, Abdalla
Key Clinical Message: Acute fulminant liver failure and acute renal failure are devastating complications caused by many drugs. The use of N‐acetylcysteine has been well established in acetaminophen toxicity, but it remains controversial in other cases. Dialysis is a very effective method of removing certain drugs from the system. With the invention of new street drugs such as "synthetic marijuana, " it may be beneficial in patients whom the substances ingested are unknown. We report a case of a 42‐year‐old male who developed acute fulminant hepatic failure and acute renal failure, who was cured with dialysis, N‐acetylcysteine, and other supportive measures. Abstract : Acute fulminant liver failure and acute renal failure are devastating complications caused by many drugs. The use of N‐acetylcysteine has been well established in acetaminophen toxicity, but it remains controversial in other cases. Dialysis is a very effective method of removing certain drugs from the system. With the invention of new street drugs such as "synthetic marijuana, " it may be beneficial in patients whom the substances ingested are unknown. We report a case of a 42‐year‐old male who developed acute fulminant hepatic failure and acute renal failure, who was cured with dialysis, N‐acetylcysteine, and other supportive measures.